Ontologi Pathet: Kajian Kritis Terhadap Pathet sebagai Representasi Norma Ontologis Transendental dalam Pergelaran Wayang - Wikandaru, Reno; Lasiyo, Lasiyo; Sayuti, Suminto A. (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2019)
Pathet is one of the most important parts in a puppet performance. Unfortunately, discussions about pathets, especially from a metaphysical perspective are very rarely found so that the wayang metaphysics is not comprehensive. This study examines the metaphysical dimensions in the puppet performance pathet in Anton Bakker's metaphysical perspective, with the aim to complete the existing puppet metaphysics studies. This research uses the methodical method of assessment, namely interpretation; induction and deduction; internal coherence; holistic; historical continuity; idealization; comparison; heuristics; inclusive or analogous language; and description, and reflection. The results of this study indicate that: first, pathet is a representation of the concept of harmony in puppet shows. Pathet is a transcendental ontological norm in puppet shows. Transcendental ontological norms, in the perspective of Anton Bakker's ontology thinking, are called harmony. In other words, it can be said that the pathet is a representation of harmony or ontological norms that apply in a puppet show. All aesthetic elements of the show are returned to the pathet, and must remain in the corridor of the applicable pathet.